2012
DOI: 10.1186/1746-1596-7-176
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous renal biopsy-induced accessory renal artery bleeding in an amyloidosis patient

Abstract: Ultrasound-guided percutaneous renal biopsy is an important technique for diagnosis of glomerular diseases, and the biopsy-induced life-threatening bleeding rarely happens. Primary systemic amyloidosis is a rare disease which may lead to organ dysfunction including arterial stiffness. The accessory renal artery is a kind of renal vascular variation which goes into the renal parenchyma directly or via the renal hilum. Here we reported a rare case of percutaneous renal biopsy-induced accessory renal artery life-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Accessory renal arteries may be injured during percutaneous renal biopsy or during other surgical procedures. Zhang Q et al [41] reported a rare case of life-threatening bleeding after percutaneous biopsy in patients with accessory renal arteries and renal amyloidosis. The presence of multiple arteries during kidney transplantation requires a longer time for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Accessory renal arteries may be injured during percutaneous renal biopsy or during other surgical procedures. Zhang Q et al [41] reported a rare case of life-threatening bleeding after percutaneous biopsy in patients with accessory renal arteries and renal amyloidosis. The presence of multiple arteries during kidney transplantation requires a longer time for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This finding encouraged us to reevaluate the role of extra renal artery flow for the development of FSGS. Previous reports showed that extra renal artery was related to various renal diseases, such as renal artery stenosis, renovascular hypertension, renal bleeding, hydronephrosis and secondary FSGS [2]. We assume that higher blood flow, which was delivered by aberrant renal artery to the lower portion of the right kidney, could produce glomerular hypertension with resultant glomerular scaring and FSGS.…”
Section: Discussionmentioning
confidence: 82%
“…In the present case, the angiographic findings were compatible with aberrant renal artery and renal biopsy injured the artery when the biopsy was performed from the lower pole of the right kidney. It was reported that significant biopsy-induced renal artery bleeding rarely occurred because renal artery was contracted when the kidney was punctured [2]. However, because of higher perfusion pressure of aberrant renal artery, vascular constriction induced by tissue biopsy could not prevent from clinically significant bleeding from the artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of renal symptoms and signs in amyloidosis is variable such as isolated proteinuria, nephrotic syndrome, hypertension, hypotension, renal insufficiency [ 16 ]. In this case, we did not practice the renal biopsy, as it has been reported that patients of amyloidosis resulted in serious bleeding over renal biopsy centesis [ 17 ]. Moreover, examinations revealed that the patient relied on a solitary right kidney as the left one was congenital dysplasia.…”
Section: Discussionmentioning
confidence: 99%